(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2018)
Gender Violence within universities has been poorly studied. Nevertheless, it is an issue that educational institutions themselves are trying to make visible, reflect upon and act accordingly. The RIIGcV (Interuniversity Network for Gender Equality and against Violence)3 promoted the creation of around protocols for discrimination and gender violence within the university environment, something that developed new debates towards these topics; evidently, it is a process still in progress. The present work aims at discussing the possibilities that higher education institutions have to guarantee free areas of discrimination and gender violence, based on the development of focused and transversal institutional policies.